IMPLEMENTATION OF THE COOPERATIVE LEARNING MODEL IN INCREASING STUDENT LEARNING MOTIVATION IN THE FIQH SUBJECT - Rahmadani Safitri, Nindi; Noprijon (Amanah Publishing, 2025)
The problem in this thesis is the low learning motivation of eighth grade students in the subject of Fiqh at Madrasah Tsanawiyah Negeri 4 Pasaman Barat. Based on initial observations and information from subject teachers, it is known that students are less active in the learning process, are not enthusiastic about the material, and have learning outcomes below standard. The purpose of this study is to describe the implementation of the cooperative learning model in increasing the learning motivation of eighth grade students in the subject of Fiqh and to determine the supporting and inhibiting factors in the application of the cooperative learning model in Fiqh learning in schools. This type of research is field research that uses a qualitative descriptive approach. This approach is appropriate to describe phenomena that occur in the field. Data collection techniques are carried out through interviews, observation, and documentation. The informants of this study are eighth grade students, the principal, and the vice principal of the curriculum department. The results of this data are carried out by testing the validity of the data using data reduction, data presentation, the author uses source triangulation. Based on the results of the study, it shows that the implementation of the cooperative learning model at Madrasah Tsanawiyah Negeri 4 Pasaman Barat can increase student learning motivation in the subject of Fiqh. The increase in motivation is seen from the increased activeness of students in the group discussion process, increased interest in the subject matter, and increased enthusiasm in completing assignments given by the teacher. Supporting factors are teacher readiness in designing and implementing learning, high student enthusiasm, the availability of adequate learning media, and support for school infrastructure. While the inhibiting factors found include low reading interest among some students, limited time in implementing cooperative learning, and the lack of variety of learning media used.